Catholicism in China, 1900-Present
XVIII, 264 p. 7 illus.
Keywords: This volume is the product of scholars of various backgrounds, specialties and agendas bringing forth their most treasured findings regarding the Chinese Catholic Church. The chapters in this book covering the church from 1900 to the present trace the development of the Church in China from many historical and disciplinary vantage points.